Development and characterization of heteropolysaccharide film - Md Dom, Nurul Syafiqah (2017)
Hydrogel is group of hydrophilic polymeric material that able to renders high amount of water in their three-dimensional network (Macneil & Rimmer, 2013). After being exposed in drying oven, the hydrogel will become film since the moisture inside hydrogel had been evaporated. Based on observation, the higher concentration of the hydrogel, the more thick and rigid the film will be produced. Besides, many heteropolysaccharides had been used as medication and also as food additives such as gelling agent to make noodle and to treat wound problem (Rathinamoorthy & Sasikala, 2011). In this study, konjac glucomannan film is produced by mix the KGM powder with distilled water and mixed using magnetic stirrer, and the physical appearance of the film produced was being investigated. Texture analyzer was being used to determine the tensile strength of the film. Meanwhile, for swelling measurements that indicate amount of water absorbed, it was being done by immersed the film in phosphated buffered saline that mimic body environment pH. The result show that film that contained high amount of konjac glucomannan has higher tensile strength and also able to absorb much amount of water that mimic the exedute that being produced during inflammation process as compared to film with low concentration.